Preferensi Pengguna Terhadap Rancangan Desain Fasilitas Integrasi Antarmoda Yang Responsif Pandemi COVID-19 Di Kawasan TOD Dukuh Atas - Daffi, Muhammad Audi; Ristianti, Novia Sari (Jurusan Perencanaan Wilayah dan Kota, 2024)
COVID-19 is a case of infectious disease that is of concern throughout the world. The intermodal integration facility as a public transportation space has the potential to become a center for the spread of the virus because of its general use. This study aims to formulate an intermodal integration facility design that is responsive to the COVID-19 pandemic in the Dukuh Atas TOD area based on its users so that they can be safe from the threat of the virus while mobilizing to meet their daily needs. This study uses quantitative methods with analytical techniques in the form of descriptive analysis to determine the design of a responsive intermodal integration facility based on the aspect of the facility. The facilities aspect discussed relates to seating arrangements, health facilities, and touch facilities. This study resulted in a design in the form of seating arrangements by limiting the user's sitting area using vegetation, promoting health facilities by providing automatic hand sanitizers placed at entrances and exits, as well as the use of modern technology on touch facilities to prevent direct contact of users with the public facilities.